2004
DOI: 10.26522/brocked.v14i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Staff-wide Mentoring of Pre-service Teachers: Benefits and Barriers

Abstract: School

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a similar vein, Smith (2004) stated that one of the beneficial results of mentor coaching is making their mentees or protégé gain collegial support.…”
Section: Findings and Discussion Mentor Coaching In Helping Pre-servimentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, Smith (2004) stated that one of the beneficial results of mentor coaching is making their mentees or protégé gain collegial support.…”
Section: Findings and Discussion Mentor Coaching In Helping Pre-servimentioning
confidence: 99%
“…Smith (2004), for instance, examined the nature of staff-wide mentoring on pre-service teacher improvement. The result of the study indicated that although there are barriers, the pre-service teachers achieved desired intensive outcomes from the mentoring program.…”
Section: Mentor Coachingmentioning
confidence: 99%
See 1 more Smart Citation